Croatian Schools Facing the Challenge of Multiculturalism - Previšić, Vlatko (Array, 1997)
After gaining the independance one of the main tasks in the process of democratization and transition in Croatia was to change its school system. This goal was hinderd by some objective circumanstances, first of all by the war and tragic postwar consequences. Designing of a "new Croatian school" presupposed the necessary curricula modernization, new legislation, statutary norms for students` and teachers` behaviour, a kind of spiritual revival. Schools have to prepare students for active democratic participation, which also means that multiculturalism has to be seen as an important and equal dialoge between people. These changes have also to be in the correlation with European achievements in the field of intercultural/multicultural education. The formal structure of the school system is only the framework for the active fuctioning of education, so the essence of the changes should be in various educational areas and school subjects. In the newly constituted states, like Croatia, there is always danger of overemphassing ethnocentrism, which could be particularly reflected in the school system. The point is how to balance it with European ideas, to evaluate them and to implement in the specific Croatian educational situation. One of the new challenges of the educational pluralism in Croatia is the introduction of private and alternative school, the process which began parallely with the democratic changes. The very important part of the school reform is creating of the new approach to the education of national minorities according to the stipulation in the new Croatian Constitution.Various forms of their education have been initiated from pre- school to the secondary school, with the special role of teachers in developing intercultural educational content. Croatian school system is really facing the challenge of multiculturalism. However, there is not still real knowledge on muliculturalism, its philosophical, religious and humanistic roots. This is why the reform of educational system in Croatia has to be more oriented towards intercultural issues.